The basis of professional competence of teachers in continuity of education - Тұрғынбаева , Ботагүл; Жайтапова, А.; Оракова, Амангул; Наметкулова, Ф.; Дүйсенбеков, Е. (Pedagogy and Psychology, 2022)
In the context of changes in the education system in Kazakhstan, the authors of the article consider the problem of developing specialists with formed professional competencies in the conditions of continuous education. It is known that the system of continuous education includes three stages: pre-professional training, professional training and postgraduate additional education. In this regard, attention is paid to problematic issues in the orientation of schoolchildren to a pedagogical specialty, the development of training programs for teachers in higher educational institutions, as well as the improvement of the professional competence of teachers in the system of advanced training, and their own conclusions are proposed. In connection with the research problem, the data of the study of school practice, the analysis of educational programs of higher educational institutions and the field of advanced training are given, an analysis of theoretical concepts is given and scientific conclusions are summarized. The article presents the author's model of qualification levels and the corresponding competencies of primary school specialists. This article was prepared within the programme trust fund study OR 11465474 «Scientific foundations of modernization of the education system and science» (2021-2023, National Academy of Education named after Y.Altynsarin). The author team thanks the Ministry of Education and Science of the Republic of Kazakhstan for the opportunity to publish this paper.